Operating systems - Nutt, Gary (Dorling Kindersley (India) Pvt. Ltd., 2009)
"Operating Systems, Third Edition has become a market leader by striking a balance between introducing the basic principles and putting examples from Linux, UNIX, and Windows into practice. The book promotes an understanding of contemporary operating system concepts and how they are applied today. For the third edition Gary Nutt has enhanced his vision with even more breadth to his coverage of operating system principles and even more opportunities for readers to see and work with real-world examples."--BOOK JACKET.